The influence of microalloying and preparation process on phase transformation, mechanical properties, and friction/corrosion behavior of Cu–Ni–Sn alloys: A review - Fei Zhou; Yanjun Zhou; Kexing Song; Yanmin Zhang; Ran Yang; Shaodan Yang; Longlong Lu; Yan Yu; Lele Liu; Jidong Chen; Kaixuan Jiang; Wenhao Yang (Journal of Materials Research and Technology, 2024)
This review provides an overview of Cu–Ni–Sn alloys, which have great advantages as a potential substitute for beryllium bronze. The characteristics of spinodal decomposition in Cu–Ni–Sn alloys are thoroughly discussed by conducting a comprehensive analysis of thermodynamics and the phase diagram. The traditional casting process for Cu–Ni–Sn alloys is subject to several limitations, including segregation during solidification as a primary constraint. Another significant limitation is the occurrence of discontinuous precipitation during aging. Thus, the strategies to overcome these limitations are further elaborated. Commonly used methods include thermal-mechanical processing and composition design. Finally, the application of Cu–Ni–Sn alloys in friction and corrosion is discussed. The purpose of this review is to provide a comprehensive summary of the research progress and significant limitations encountered in Cu–Ni–Sn spinodal alloys. This includes a discussion of traditional casting methods as well as novel preparation techniques. The aim is to serve as a valuable reference for the development of new manufacturing methods and the future advancement of Cu–Ni–Sn spinodal alloys.